Titanium dioxide nanostructure-loaded Adriamycin surmounts resistance in breast cancer therapy: ABCA/P53/C-myc crosstalk - Rehab M Abdel-Megeed; Abdel-Hamid Z Abdel-Hamid; Mai O Kadry (Future Science OA)
Aim: To clarify the alternation of gene expression responsible for resistance of Adriamycin (ADR) in rats, in addition to investigation of a novel promising drug-delivery system using titanium dioxide nanoparticles loaded with ADR (TiO2-ADR). Method: Breast cancer was induced in female Sprague-Dawley rats, followed by treatment with ADR (5 mg/kg) or TiO2-ADR (2 mg/kg) for 1 month. Results: Significant improvements in both zinc and calcium levels were observed with TiO2-ADR treatment. Gene expression of ATP-binding cassette transporter membrane proteins (ABCA1 & ABCG1), P53 and Jak-2 showed a significant reduction and overexpression of the C-myc in breast cancer-induced rats. TiO2-ADR demonstrated a notable ability to upregulate these genes. Conclusion: TiO2-ADR could be a promising drug-delivery system for breast cancer therapy.